DAYA TAHAN 109 JENIS KAYU INDONESIA TERHADAP RAYAP TANAH (Coptotermes curvignathus Holmgren) - Ginuk Sumarni; Han Roliadi (Jurnal Penelitian Hasil Hutan, 2002)
The resistance of 109 Indonesian wood against subterranean termite (Coptotermes curvignathus Holmgren) attack has been assesed. The wood species come from several regions in lndonesia. The woods were each cut to small samples measuring to 2.5-cm by 2.5-cm by 0.5-cm and subsequently exposed to 200 subterranean termite workers for four weeks.The results revealed that 68 out the 109 wood species (i.e.62.3 percent) were classified as themost durable (classes I and II): and the rest, i.e 41 species (37.8 percent), were classified as lower durability (i.e. classes Ill, IV, and V) and therefore in their application need a preservative treatment.